PENEGAKAN HUKUM TINDAK PIDANA KORUPSI YANG BERUPA PENERIMAAN GRATIFIKASI SEBAGAI SUAP - Sunarto Sunarto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
The phenomenon of gratification today is so endemic and leads to pathological symptoms, which is a condition in which corruption and gratification have been regarded as